(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The use of technology in the Digital Era in the world of education is needed to facilitate the assessment of students, be it cognitive competence, psychomotor and even character assessment contained in affective competence. SIHEBAT is a digital platform developed by researchers in learning to conduct character assessments in students. The researcher conducted research on the development of the SIHEBAT platform on the learning process of students at SDN 2 Sukamurni. This study aims to 1) how to develop this SIHEBAT platform in the assessment of the 7 habits of great Indonesian children in elementary school, and 2) how this SIHEBAT platform can be applied in the assessment of the 7 habits of Indonesian children in elementary school. The type of research used is Research and Development (R&D), and the research model uses D&D which contains the EDDIE stage, namely Design and Development with a qualitative approach. The population in this study is 8 teachers at SDN 2 Sukamurni, Cilawu district, Garut regency using purposive sampling. The data collection technique used was non-test with documentation studies, interviews and questionnaires. The technical data analysis carried out in this study is a quantitative descriptive analysis, with validation tests, feasibility tests and acceptance tests. The results of the study show that the SIHEBAT digital platform obtained a "feasible" assessment in the content domain and "very feasible" in the construction domain and has a very high level of acceptanceof the user. From the material experts, seven habits of great Indonesian children obtained a score of 91.25% with the interpretation of the material very feasible to use. This proves that the results of the research can answer the problem and make a positive contribution to the assessment of the seven habits of great Indonesian children in elementary schools.